Rekognisi Penghayat Kepercayaan dalam Perspektif Teori Pengakuan Axel Honneth - Tarisha, Inaya; Farah Zannuba, Iftitah; Puspita Sari , Audina; Tirta Niagara, Raung; Muhammad Noor, Aditia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Agama Islam Miftahul Ula (STAIM) Kabupaten Nganjuk, Indonesia., 2025)
The obstacles that occur in the context of religion and penghayat kepercayaan are not over. There is a theory of recognition proposed by Axel Honneth to strengthen the argument for the recognition of penghayat kepercayaan, it is necessary to know how the relation of penghayat kepercayaan recognition in Indonesia with Honneth's perspective. This research is conducted using qualitative method which is presented in descriptive form. The conclusion obtained from the discussion of this research is that the concept of penghayat kepercayaan in Indonesia has not received the same rights as other religious adherents, especially in terms of administration, even with the Constitutional Court decision No. 97/PUU-XIV/2016. Based on Honneth's perspective, recognition has three patterns to realize it that are interconnected, namely love patterns, legal patterns, and solidarity patterns. This research found that the existing legal framework is not sufficient for the adherents of penghayat kepercayaan. The hope for the realization of real recognition of indigenous faiths turns out to experience a lot of missrecognition. Recognition of each individual belief identity is included in the context of human rights, so the struggle for the recognition of indigenous faiths is worth fighting for.